TO BE IS NOT-TO-BE: NIHILISM, IDEOLOGY AND THE QUESTION OF BEING IN HEIDEGGER’S POLITICAL PHILOSOPHY PART II: TRUTH, HUMANISM AND TECHNOLOGY - Mihai NOVAC (Challenges of the Knowledge Society, 2016)
Allegedly, Heidegger never quite finished Being and Time: his initial intention had consisted in the determination of the meaning of Being as such, apart from Dasein’s own existentiality. Afterwards, however, and despite the growing public excitement revolving around the published unfinished version of his project, his preoccupations, thematic conceptuality and very language, apparently started to shift away towards a strange and unfamiliar stance which he would never leave. Quite surely, his Nazi flirtation and subsequent withdrawal did not help in bringing clarity over this. On the other hand, this was not necessarily unexpected (although not necessarily to be expected, as well). What I mean to say is that for someone reading Being and time in spirit and not in law, the possibility of such a substantive rethought of his initial scheme is present throughout the work. One’s changing one’s mind with respect to oneself is, after all, one of the basic possibilities conveyed by Dasein’s achieved resoluteness [Entschlossenheit]. Furthermore, despite his apparent reorientation, I think we can speak of some sort of attitudinal unity between Heidegger’s initial and later work, conceptually mediated by the relationship between Dasein’s Being-unto-death [Sein-zum-Tode] and the so called concealedness [Verborgenheit] of Being.. That is precisely what I aim to lay bare through this conceptual reconstruction of some of his later works: (i) On the Essence of Truth (1930) and (ii) Letter on Humanism (1946). Basically, I will try to show that if in Being and Time he tried to come to Being from Dasein, in his later work he tries to get to Da-sein from Being, fact which unsurprisingly brought along some reconsiderations but that, broadly speaking, essentially amounts to what he set out to do in his initial ontological project. Surprisingly, the most concrete instance of this pendulation between Dasein and Being is to be found, at least to my knowledge, in one of his more political works, i.e. (iii) The Question Concerning Technology (1953), around which our present endeavor will mostly revolve.